The Seven Tools of Causal Inference, with Reflections on Machine Learning. - PEARL, JUDEA (Communications of the ACM, 2019)
The article discusses the seven tools of causal interference and offers reflections on machine learning. Topics include encoding causal assumptions, the algorithmitization of counterfactuals, and mediation analysis and the assessment of direct and indirect effects.